2008
DOI: 10.1371/journal.pgen.0030236
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the Ancestry of European Americans in Genetic Association Studies

Abstract: European Americans are often treated as a homogeneous group, but in fact form a structured population due to historical immigration of diverse source populations. Discerning the ancestry of European Americans genotyped in association studies is important in order to prevent false-positive or false-negative associations due to population stratification and to identify genetic variants whose contribution to disease risk differs across European ancestries. Here, we investigate empirical patterns of population str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
238
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(256 citation statements)
references
References 33 publications
(60 reference statements)
16
238
1
1
Order By: Relevance
“…34,44,45 We extend these observations by showing that a local European-American population is already subtly distinct from its European sources. We found that European Americans exhibit visibly greater dispersion along higher-order PCs than Europeans (Figure 2b and Supplementary Figures S5 and S6) despite marginal values of F ST (Table 2) and continued coincidence between the groups along top PCs (Figure 2a and Supplementary Figure S4).…”
Section: Similarity and Divergence Between Central Wisconsin And Europesupporting
confidence: 54%
“…34,44,45 We extend these observations by showing that a local European-American population is already subtly distinct from its European sources. We found that European Americans exhibit visibly greater dispersion along higher-order PCs than Europeans (Figure 2b and Supplementary Figures S5 and S6) despite marginal values of F ST (Table 2) and continued coincidence between the groups along top PCs (Figure 2a and Supplementary Figure S4).…”
Section: Similarity and Divergence Between Central Wisconsin And Europesupporting
confidence: 54%
“…We propose two applications 5,26 for this AIMs panel: (1) to evaluate study design before starting GWAS, for example, by genotyping cases and controls on this panel, we can remove unsuitable cases and controls; (2) to be used for genotyping in targeted association studies, such as CGAS or replication studies following GWAS, in which variants are targeted in a large number of samples that have not been densely genotyped. Our AIMs panel can be used to efficiently correct for stratification using methods such as EIGENSTRAT not genomic control procedure, to ensure that the observed associations are not spurious without relying on self-reported ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…To discern the ancestry of Europeans or European Americans, multiple sets of AIMs have been established that allow correction for population stratification in association studies using Europeans. [5][6][7] Recently, a great number of genetic association studies on various diseases have been conducted on non-European populations.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary Jewish communities have been genetically analyzed both from population genetics and medical perspectives by means of uniparental and recombining markers, [10][11][12][13][14][15][16][17] and more recently also through genome-wide approaches. [18][19][20][21][22][23] However, only a few reports have been published on Sephardic and crypto-Jewish descendants.…”
Section: Introductionmentioning
confidence: 99%